Urbanisasi di Kota Balikpapan: Formasi Sosial Keluarga Pendatang Miskin - Mutmainnah, A. Nurul; Kolopaking, Lala M.; Wahyuni, Ekawati Sri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Gadjah Mada, 2014)
The research aimed to explain the urbanization in Balikpapan City and the poverty that faced by the needy migrant family through their social and formation processes what their experience. Methods use in the research from quantitative and qualitative method. The research was using the primary data through survey, in-depth interview and field log book. The secondary data are use from documentation and related articles to explain the urbanization in Balikpapan City. The result shown that, the urbanization in Balikpapan City connected with the present of the needy family from various regions in Indonesia that seek for jobs. The solidarity among ethnic, become one of the social process that experience by the needy family. The needy migrant families that bond with ethnic bond, than use by the financier as cheap labor that make the migrant family still in poverty.